Menumbuhkembangkan Jiwa Wirausaha Melalui Kegiatan Mini Festival UMKM Desa: Studi Kasus di Desa Datar Kec.Warungpring Pemalang - Hendri Sucipto; Slamet Bambang Riono; Muhammad Syaifulloh (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to evaluate the impact of the MSME mini festival activities on the development of an entrepreneurial spirit in Datar Village, Warungpring District, Pemalang Regency. This mini festival is designed to promote local Micro, Small and Medium Enterprises (MSME) products and provide a platform for MSME players to interact with visitors and participants. By involving various activities, such as product exhibitions, entrepreneurial workshops, and art performances, this festival is expected to encourage the entrepreneurial spirit, improve business skills, and expand the market for MSME products. The research methodology includes qualitative and quantitative approaches with data collection through surveys, interviews and observations. The survey was conducted to measure changes in motivation and entrepreneurial skills of MSME actors before and after the festival. Interviews were conducted with MSME actors, visitors and festival committee members to gain insight into the impact of the festival. Observations were carried out during the festival to assess the interactions and activities that took place. The research results show that the mini festival has a significant positive impact on the development of an entrepreneurial spirit among MSME players. This festival succeeded in increasing the motivation of MSME players to innovate and develop their products, with an average increase in motivation. Apart from that, the business skills of MSME players also experienced improvements, especially in terms of marketing and financial management. The mini festival also succeeded in expanding the market for MSME products and increasing the visibility of local products.